Relationship of Mindful Eating with Healthy Lifestyle Factors and Emotion - Ringle, Ellen (My University, 2014)
There is growing interest in dispositional mindfulness and its impact on health and wellbeing. Mindful eating may be a component of maintaining healthy lifestyles. 143 college students completed a mindful-eating questionnaire (MEQ), 3-day dietary intake and physical activity recall, and measure of emotions. MEQ scores were higher among participants with a healthy BMI compared to unhealthy BMI. Only the emotional subscore of mindful eating (MEQ-EM) was positively correlated with dietary quality with marginal significance. Higher levels of positive emotion were significantly directly correlated with higher MEQ-EM score, better dietary quality, and higher levels of physical activity. Findings were supportive of the significance of a mindful eating component in healthy lifestyles. An intervention-based study is necessary to determine sequential relationship of these factors.